Population and seascape genomics of a critically endangered benthic elasmobranch, the blue skate Dipturus batis - Delaval, Aurelien Nicolas; Frost, Michelle; Bendall, Victoria; Hetherington, Stuart J.; Stirling, David; Hoarau, Galice Guillaume; Jones, Catherine S.; Noble, Leslie Robert (Evolutionary Applications, 2021)
publishedVersion